Anycast routing in time-expanded vehicular networks. (March 2020) - Amirshahi, Alireza; Romoozi, Morteza; Raayatpanah, Mohammad Ali; Asghari, Seyyed Amir
Abstract: Anycast is an important type of communication pattern to deliver a message to at least one best destination node within a set of multiple potential destinations. This approach is a challenging problem due to finding the best destination or a subset of potential destination sets, especially in multi-hop networks. In this paper, we consider this problem of determining the minimum cost anycast path in vehicular networks with three different scenarios, which are exactly-one, at-least-one and K-anycast scenario. The dynamic topology of vehicular network makes the mathematical modeling difficult. To formulate the problem on these scenarios, mixed-integer linear programming models were presented by using auxiliary time-expanded network. Finally, the models were analyzed and the metrics were evaluated in each scenario. The results indicate that the more delivery ratio in exactly-one scenario and lower cost, hop count and delay than other scenarios.